Knowledge and Attitudes Towards Mental Health Conditions among Pharmacy Interns of Specialized Hospital - dela Cruz, Joanna Mae; Orfanel-Fabon, Eden; Gatpo, Madelane; Mativo, Cynthia; Malang, Bernandino (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this study is to determine the knowledge and attitudes toward mental health conditions of Pharmacy Interns in Specialized Hospital, and the role of demographic characteristics needs to be considered when investigating stigma and its relationship to mental health knowledge. Finally, align and formulate programs for Pharmacy Internship in Specialized Hospital to strengthen the positive attitudes and mitigate the negative attitudes toward mental health further. The Mental Illness: Clinician's Attitudes Scale (Medical Student Version MICA-2) and the Mental Health Knowledge Schedule (MAKS) were completed by 25 Pharmacy Interns of Specialized Hospitals. Descriptive statistics were done to describe differences in demographic characteristics. Parametric Test Pearson R was used to assess the relationship between the knowledge and attitudes of Pharmacy Interns. The Analysis of Variance (ANOVA) was the test used to compare the variations in total scores between MICA and MAKS based on various demographic factors. This study revealed that pharmacy interns of specialized hospitals have a generally positive attitude and are knowledgeable about mental health conditions. In this study, having more mental health knowledge correlates with a less stigmatizing attitude. There was a significant difference in the attitude of Pharmacy Interns when grouped according to their educational attainment. As a recommendation, evaluation after the Pharmacy Internship through MICA and MAKS can be done. Also, Specialized Hospitals should consider implementing intervention programs to advance mental health knowledge and positive attitudes among Pharmacy Interns.